Penerapan Algoritma Greedy Untuk Menyelesaikan Permasalahan Integer Knapsack (Studi Kasus : Indah Logistik Cargo Mataram) - Setiawati, Setiawati; Fitrawati, Elyin; Awwaliyah, Razma Rizqiyah; Alivia, Baiq Nadiva; Bahri, Syamsul (Program Studi Matematika, 2024)
Distribution is one form of problem that can be solved using the optimization process. There are various things that can be optimized in distribution problems, including maximizing the weight of goods to be distributed so that it can save distribution costs and provide benefits for the company. One of the companies engaged in the distribution of goods is Indah Logistik Cargo, Mataram branch, where in the distribution process there are goods with quantities that exceed the capacity of the shipping equipment. Therefore, it is necessary to select goods to be delivered with the maximum weight but not exceeding the capacity that provides greater benefits to the company. This problem is one of the integer knapsack problems. In this study, researchers used greedy algorithms, namely greedy by profit, greedy by weigth and greedy by density to optimize profits. From the research results, it is obtained that the method that has a greater profit in the distribution process at Indah Logistik Cargo Mataram is greedy by density, which amounts to ?? 2,603,138.3.